Effect of creep feeding and creep diet on pre- and post-weaning pig performance - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1983)
Three trials involving 61 litters of pigs were conducted to evaluate the effects of creep feeding and creep diet on weaning weight and subsequent performance in the nursery. Pigs offered a commercial milk replacer pellet (Soweena Pig Pellets) consumed more feed and were heavier at weaning than pigs fed a 20% whey corn-soybean meal creep diet or pigs fed no creep feed. Pigs utilized the creep feed very efficiently with creep feed conversion rates of less than 1:1. Creep feeding did not affect the 4- or 5-week post-weaning average daily gain or feed conversion. However, pigs that were creep fed and heavier at weaning also were heavier at 8 to 9 weeks of age.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Creep feeding; Creep diet; Pig performance